2004
DOI: 10.1080/09540260310001635168
|View full text |Cite
|
Sign up to set email alerts
|

Lithuania mental health country profile

Abstract: As a part of international mental health policy, programmes and services project, the 'country profile' instrument was used for assessment of mental health policy and services in the Republic of Lithuania. Analysis of contextual factors revealed high levels of social pathology (including violence, suicide and other self-destructive behaviour) with stigmatizing approaches by the general population to mentally disturbed persons and other vulnerable groups. Analysis of existing data about resources invested in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
28
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 0 publications
0
28
0
1
Order By: Relevance
“…It was introduced only in the early 1990, after the Soviet Union collapsed (Pūras et al 2004). This scoping review revealed that research on autism is limited.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It was introduced only in the early 1990, after the Soviet Union collapsed (Pūras et al 2004). This scoping review revealed that research on autism is limited.…”
Section: Discussionmentioning
confidence: 99%
“…Little is known about the current situation of autism in Baltic States as there is a lack of substantial research in this field across all three Baltic countries (Pūras et al 2004;Querdenker and Meirhofer 2014;Mikulėnaitė and Ulevičiūtė 2004). Therefore, to investigate autism in this region, we decided to perform scoping review.…”
mentioning
confidence: 99%
See 3 more Smart Citations